STUDIES ON AN AGGLUTINOGEN (Rh) IN HUMAN BLOOD REACTING WITH ANTI-RHESUS SERA AND WITH HUMAN ISOANTIBODIES - Landsteiner, Karl (The Rockefeller University Press, 1941)
Studies are reported on an individual agglutinogen (Rh) in human blood which has been found to be of clinical importance because occasionally it gives rise to the formation of immune isoantibodies in man, a peculiarity which leads to untoward transfusion reactions. A method for the determination of the presence or absence of the new blood factor is described, which can be used for typing patients and prospective blood donors. Examination of families showed that the agglutinogen is inherited as a simple Mendelian dominant. The distribution of the factor Rh among white individuals and negroes may indicate racial differences. The property is probably genetically independent of the blood groups and the factors M and N.